Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - 8-5 Factoring X(squared) + bx + c - Mixed Review - Page 505: 67



Work Step by Step

In order to simplify the product (3w+7)(3w-7) we must apply the rule that states that (a+b)(a-b)=$a^{2}$-$b^{2}$, and we'll set a=3w and b=7. Therefore, (3w+7)(3w-7)=$(9w)^{2}$-$7^{2}$ =81$w^{2}$-49
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.